Prospects for Digitalization of Public Administration Processes - V. A. Plotnikov; A. V. Maslyuk (Управленческое консультирование, 2022)
The subject of consideration in this article are the state and prospects for the digitalization of public administration in modern Russia. The scale and speed of changes in all spheres of public relations caused by digital technologies is unprecedented, these changes were especially accelerated during the Covid-19 pandemic. They affect these changes and processes of public administration, at the same time, in this area there are differences from the commercial sector, where such a phenomenon as the “digital economy” has arisen and is developing. The task of the modern state is to create digital services and platforms aimed at more rapid and high-quality satisfaction of the needs of citizens and business, that is, in essence —to generate a new type of public goods in the form of digital public services. The article considers the prospects for the development of such processes.